KETERAMPILAN BERPIKIR TINGKAT TINGGI DALAM MEMECAHKAN DERET ARITMATIKA DUA DIMENSI BERDASARKAN TAKSONOMI BLOOM - Zainal Abidin; Mohammad Tohir (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2019)
The research aims to describe the level of higher-order thinking skills ability of students in solving generalization patterns in two-dimensional arithmetic series based on revised Bloom's taxonomy. The research method used is a qualitative descriptive approach. The subjects were students of the Master Program of Mathematics Education at Jember University. The data was collected by giving open problem-solving tasks and documentation studies to students to develop patterns of one-dimensional arithmetic series. Then, students are given the task of solving the next problem to draw up a generalization pattern of two-dimensional arithmetic series. The data analysis technique used is qualitative descriptive data analysis. The results showed that the percentage of higher-order thinking skills aspects included analyze (C4) reached 88.89%, evaluate (C5) reached 83.33%, and create (C6) reached 66.67%. The results of this achievement are influenced by several factors, including accuracy in compiling numbers and expanding existing data, mastery of arithmetic series permutation concepts and their application, the tendency of graduate students to rely on memorization and imitations of existing examples.